Analisis Perubahan Kebijakan Impor Skrap Plastik Indonesia Dari Negara-Negara Maju Tahun 2016-2019 - Pramesti, Maghfira Raudya; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Indonesia has a problem in effort to fulfill these raw materials of plastic industries, plastic scrap containers were sent back to their countries of origin and a change of plastic scrap import policies in Indonesia. The entry of plastic waste between imported plastic scrap containers is due to the impact of China which has implemented the National Sword policy. The entry of plastic waste illegally in Indonesia is not matched by proper management of plastic waste recycling system, causing accumulation and burning of plastic waste which can affect Indonesia's environment. The purpose of this study is to determine the reasons behind the changes in plastic scrap import policy made by Indonesia. Types of the research is explanative and qualitative with the literature study method. In analyzing the policy changes made by Indonesia, this study uses Environmental Security theory and Rational Actor Model theory to find out the rational reasons for Indonesia to change its plastic scrap import policy in 2019. The results of this study indicate that changes in plastic scrap import policy made by Indonesia are based on the national interest to protect Indonesia's environmental sustainability, as well as any change options have compared the profit and loss.